2016
DOI: 10.1111/josi.12159
|View full text |Cite
|
Sign up to set email alerts
|

Resource Scarcity and Prescriptive Attitudes Generate Subtle, Intergenerational Older‐Worker Exclusion

Abstract: Prior work describes specific, prescriptive resource tensions between generations, comprising active Succession, passive Consumption, and symbolic Identity (SCI; North & Fiske, 2013a, 2013b). The current paper focuses on how these domains potentially drive intergenerational exclusion in work-related networking and training spheres. Studies 1a–1c—each focusing on a different SCI domain—manipulated perceived resource availability between generations, then introduced a professional networking opportunity. Across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 48 publications
3
87
0
5
Order By: Relevance
“…Shifts in the growing aging population along with a youth‐centered focus in many cultures point to the need to focus not just on ageist attitudes, but also on intergenerational relations. North and Fiske (, ) have developed an individual differences measure, Prescriptive Intergenerational–Tension Ageism Scale, to help disentangle the nature and scope of intergeneration relations, and its three subscales (Succession, Identity, and Consumption) allowing for a fine‐grained analysis of such relations. In their study of 18‐ to 75‐year‐old participants, North and Fiske (), showed that younger participants in their study who agreed more with the succession subscale (that older workers should turn over resources to younger workers) reported wanting to invest less in older worker training.…”
Section: Subthemes In the Expansion Of The Understanding Of Ageismmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts in the growing aging population along with a youth‐centered focus in many cultures point to the need to focus not just on ageist attitudes, but also on intergenerational relations. North and Fiske (, ) have developed an individual differences measure, Prescriptive Intergenerational–Tension Ageism Scale, to help disentangle the nature and scope of intergeneration relations, and its three subscales (Succession, Identity, and Consumption) allowing for a fine‐grained analysis of such relations. In their study of 18‐ to 75‐year‐old participants, North and Fiske (), showed that younger participants in their study who agreed more with the succession subscale (that older workers should turn over resources to younger workers) reported wanting to invest less in older worker training.…”
Section: Subthemes In the Expansion Of The Understanding Of Ageismmentioning
confidence: 99%
“…Abrams et al. () and North and Fiske () offer new insights into the persistent problem of age discrimination in the international workforce. In the Abrams et al.…”
Section: Subthemes In the Expansion Of The Understanding Of Ageismmentioning
confidence: 99%
“…For instance, they are frequently perceived as having lower mental and physical ability and being poorer performers than younger workers; they are also judged as less motivated, less productive, less adaptable, and less willing to change and learn (Ng & Feldman, ; Posthuma & Campion, ). These prejudices generally contradict empirical evidence (Ng & Feldman, , ; Posthuma & Campion, ), but they nonetheless have significant effects upon older workers: they operate as barriers to older workers’ employment, training and promotion opportunities, especially under conditions of resource scarcity (Gordon & Arvey, ; North & Fiske, ). They also make older workers susceptible to stereotype threat, which worsens their performance, attitudes, and well‐being at work (Abrams, Eller, & Bryant, ; von Hippel, Kalokerinos, & Henry, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, analyses of legal claims (von Schrader and Nazarov, 2015), workforce surveys (e.g., Kelly Services, 2006), and experimental as well as field studies (e.g., Gordon and Arvey, 2004; Bal et al, 2011) suggest that organizations have not yet reached this goal: discrimination against older workers is prevalent, particularly at hiring. In fact, organizations are reluctant to invest in older workers (North and Fiske, 2016) and show bias in hiring older workers (Abrams et al, 2016), especially older female workers (Neumark et al, 2015). Often, the age bias goes back to negative stereotypes about older workers that are activated when recruiters learn about the age of the job candidate (Perry et al, 1996; Shore and Goldberg, 2005).…”
Section: Introductionmentioning
confidence: 99%